The numerical investigations of SiGe/Si heterojunction electro-optic modulator in mid-infrared - Feng, Song; Hu, Xiangjian; Feng, Lulu; Wang, Di; Chen, Menglin; Liu, Yong; Hu, Heming; Jia, Lianxi (Frontiers in Physics, 2022)
We present the detailed numerical analysis and characterization of SiGe/Si heterojunction electro-optic modulator at 2 μm, 4.3 μm, and 5 μm wavelengths. We investigate the band, the refractive index, and the carrier injection efficiency of SiGe/Si heterojunction PIN electrical structure. Numerical investigations are carried out on the key geometrical parameters, doping concentration, Ge content. The results show that the modulated voltage of SiGe/Si PIN heterojunction modulator is lower 50% than that of Si modulator under the same modulation effect. In order to eliminate the absorption losses of SiO2 in mid-infrared, the punch Mach–Zehnder optical structure is established and researched. The research present that the modulator has the short 500µm phase shifters and the low VπLπ of 0.042 V·cm under forward bias voltage, and the extinction ratio is greater than 12.81 dB. The high-speed transmission characteristics are shown to have clean eye diagrams up to 40 Gbps in mid-infrared.